If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-3) + -17(-5) = 0 -3 + -17(-5) = 0 Multiply -17 * -5 -3 + 85 = 0 Combine like terms: -3 + 85 = 82 82 = 0 Solving 82 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 6(1-2m)=-6(m+4) | | 4x-12=92 | | 3+2m=n | | 120=72+60x-12x^2 | | 15x-2=4c-13 | | 12=-4(-6c-3) | | 3x+8*x=300 | | 0.4(x-5)=0.2(10-12x)+x | | =(4r-5)(7r+2) | | 3000=9.48h-(1.1376h) | | -3(8z+6)= | | 1.2x+1=0 | | 2(x-3)-(x+1)=28 | | 15x-3(3x-3+4)=6 | | 2(w-6)=3w | | -3(4x+3)+24x=39 | | 6-y/2=4 | | 2x-2/5x-10 | | -4n-4(4n-3)=5n-4(n-3) | | -4c-3(c-12)=20 | | -9/4a=18 | | (-3)-11x=52 | | 2/5x-7=11 | | -2x-3+3x=12 | | (2/3)x^2-8=19 | | 1500b=10500 | | 2x-17=28-3x | | -7x+9=-5x+17 | | 3y+10=67 | | 18*0.83-21y=15 | | 5x=82 | | 30x=-27x-63 |